Influence of Aggregated Powder Structures on Sintering Behaviour of Multilayer Hydroxyapatite Laminates - Hahn, E.; Hum, Jasmin; Will, Julia; Zuo, K.; Jiang, D.; Greil, Peter (Journal of Ceramic Science and Technology, 2011)
Aqueous tape-cast slurries of hydroxyapatite with a solid loading of 32 vol% were prepared from various fractions of aggregated (mean particle size 4.7-5.6 mu m) and dispersed powder (mean particle size 0.17-0.29 mu m). Multilayer laminates were prepared and the shrinkage and density of the laminates sintered at 1250 degrees C were measured. While fractional density in the green laminates remains almost constant at 0.52, a pronounced increase in fractional sintered density from 0.96 to >0.99 was observed with decreasing fraction of aggregated powder. Residual pore size and pore number density were reduced from 0.58 mu m to 0.48 mu m and 0.049 pores/mu m(2) to 0.019 pores/mu m(2), respectively. The multilayer laminates attained a mean bending strength of 118 +/- 10 MPa measured with the bi-axial bending test. An osteosynthesis plate design was fabricated for demonstration of the potential of sintered multilayer laminates.
Keywords: Hydroxyapatite; laminate sintering; aggregated and dispersed powder